N6-methyladenosine upregulates ribosome biogenesis in environmental carcinogenesis - Zhao, Tianhe; Sun, Donglei; Long, Keyan; Lemos, Bernardo; Zhang, Qian; Man, Jin; Zhao, Manyu; Zhang, Zunzhen (The Science of the total environment, 2023)
Many trace metal pollutants in surface water, the atmosphere, and soil are carcinogenic, and ribosome biogenesis plays an important role in the carcinogenicity of heavy metals. However, the contradiction between upregulated ribosome biogenesis and decreased ribosomal DNA copy number in environmental carcinogenesis is not fully understood. Here, from a perspective of the most predominant and abundant RNA epigenetic modification, N6-methyladenosine (m6A), we explored the reason behind this contradiction at the post-transcriptional level using arsenite-induced skin carcinogenesis models both in vitro and in vivo. Based on the m6A microarray assay and a series of experiments, we found for the first time that the elevated m6A in arsenite-induced transformation is mainly enriched in the genes regulating ribosome biogenesis. m6A upregulates ribosome biogenesis post-transcriptionally by stabilizing ribosomal proteins and modulating non-coding RNAs targeting ribosomal RNAs and proteins, leading to arsenite-induced skin carcinogenesis. Using multi-omics analysis of human subjects and experimental validation, we identified an unconventional role of a well-known key proliferative signaling node AKT1 as a vital mediator between m6A and ribosome biogenesis in arsenic carcinogenesis. m6A activates AKT1 and transmits proliferative signals to ribosome biogenesis, exacerbating the upregulation of ribosome biogenesis in arsenite-transformed keratinocytes. Similarly, m6A promotes cell proliferation by upregulating ribosome biogenesis in cell transformation induced by carcinogenic heavy metals (chromium and nickel). Importantly, inhibiting m6A reduces ribosome biogenesis. Targeted inhibition of m6A-upregulated ribosome biogenesis effectively prevents cell transformation induced by trace metals (arsenic, chromium, and nickel). Our results reveal the mechanism of ribosome biogenesis upregulated by m6A in the carcinogenesis of trace metal pollutants. From the perspective of RNA epigenetics, our study improves our understanding of the contradiction between upregulated ribosome biogenesis and decreased ribosomal DNA copy number in the carcinogenesis of environmental carcinogens. [Display omitted] •m6A in arsenic carcinogenesis is enriched in the genes regulating ribosome biogenesis.•m6A promotes ribosome biogenesis by affecting ribosomal proteins and non-coding RNAs.•m6A transmits proliferative signals to ribosome biogenesis by activating key node AKT.•m6A also upregulates ribosome biogenesis in chromium or nickel-induced transformation.•Inhibiting m6A-upregulated ribosome biogenesis blocks environmental carcinogenesis.